High-Temperature Short-Time Pasteurization System for Donor Milk in a Human Milk Bank Setting - Escuder-Vieco, Diana; Espinosa-Martos, Irene; Rodríguez, Juan M.; Corzo, Nieves; Montilla, Antonia; Siegfried, Pablo; Pallás-Alonso, Carmen R.; Fernández, Leónides (Frontiers in Microbiology, 2018)
Donor milk is the best alternative for the feeding of preterm newborns when mother’s own milk is unavailable. For safety reasons, it is usually pasteurized by the Holder method (62.5ºC for 30 min). Holder pasteurization results in a microbiological safe product but impairs the activity of many biologically active compounds such as immunoglobulins, enzymes, cytokines, growth factors, hormones or oxidative stress markers. High-temperature short-time (HTST) pasteurization has been proposed as an alternative for a better preservation of some of the biological components of human milk although, at present, there is no equipment available to perform this treatment under the current conditions of a human milk bank. In this work, the specific needs of a human milk bank setting were considered to design an HTST equipment for the continuous and adaptable (time-temperature combination) processing of donor milk. Microbiological quality, activity of indicator enzymes and indices for thermal damage of milk were evaluated before and after HTST treatment of 14 batches of donor milk using different temperature and time combinations and compared to the results obtained after Holder pasteurization. The HTST system has accurate and simple operation, allows the pasteurization of variable amounts of donor milk and reduces processing time and labor force. HTST processing at 72ºC for, at least, 10 s efficiently destroyed all vegetative forms of microorganisms present initially in raw donor milk although sporulated Bacillus sp. survived this treatment. Alkaline phosphatase was completely destroyed after HTST processing at 72 and 75ºC, but γ-glutamil transpeptidase showed higher thermoresistance. Furosine concentrations in HTST-treated donor milk were lower than after Holder pasteurization and lactulose content for HTST-treated donor milk was below the detection limit of analytical method (10 mg/L). In conclusion, processing of donor milk at 72ºC for at least 10 s in this HTST system allows to achieve the microbiological safety objectives established in the milk bank while having a lower impact regarding the heat damage of the milk.